Selective process of zinc extraction from spent Zn–MnO2 batteries by ammonium chloride leaching - Nogueira, Carlos (2016)
Recycling of spent Zn-MnO2 batteries by hydrometallurgy is usually carried out by leaching in acid media, mainly with sulphuric acid solutions. Another type of leachant was used in this work, specifically solutions of concentrated ammonium chloride. The development of this study has relied on the prediction of the chemical behavior of the constituting phases based on data obtained from theoretical and experimental equilibrium values. The assessment of the effects of factors on leaching efficiency was also done. It was concluded that about 70% of zinc, as ZnO, can be selectively extracted using this media, under optimized conditions such as 4-5 M NH4Cl, 90-100 °C and 4 h, the remaining zinc namely that corresponding to the spinel form ZnO·Mn2O3 being insoluble. All other manganese species were also almost insoluble, besides iron, holding up that ammonium chloride leaching is a very selective process for zinc recovery from batteries. The factors temperature, leachant concentration and time are indicate to be very significant in leaching, while stirring velocity was less relevant. The apparent activation energy was calculated based on the initial velocity differential method and the value achieved (5.7 ± 0.7 kcal mol- 1) showed a mixed control process. This indicates that, although the surface chemical reaction is still playing an important role in the leaching mechanism, the contribution of diffusion phenomena shall not be disregarded at all.